Characteristics of a novel lentivirus derived from South African sheep with pulmonary adenocarcinoma (jaagsiekte) - Quérat, G; Barban, V; Sauze, N; Vigne, R; Payne, A; York, D; De Villiers, E M; Verwoerd, D W (Virology (New York, N.Y.), 1987)
A novel lentivirus was isolated from South African sheep with experimentally transmitted lung adenocarcinoma. Similar to visna virus and caprine arthritis encephalitis virus, this new strain induced cytopathic effects on ovine plexus choroid cultures. In contrast to a recent Israeli isolate from sheep with adenocarcinoma, the South African lentivirus could not transform fibroblast cultures. The antigenic relatedness between the new isolate and visna virus was assessed by immunoprecipitation of radiolabeled viral proteins, using monospecific antisera against visna virus proteins. The results indicate that the new virus contains four major structural proteins of sizes similar to those of visna virus (i.e., gp135, p30, p16, and p14) and have some common antigenic determinants (about 90% in the major core antigen p30). However, the nucleotidic sequences of the novel lentivirus were found to be only 16.5 to 27.4% homologous to visna virus and 8.3 to 15% homologous to caprine arthritis encephalitis virus, by means of liquid hybridization under stringent conditions. The genetic divergence indicated by this last result was confirmed by the dissimilar restriction endonuclease cleavage map of the new virus in comparison to those of visna virus and three caprine arthritis encephalitis virus strains. The demonstration of a third type of ovine lentivirus supports the concept of an important genetic variation among the lentiviruses infecting one animal species.